Mycorrhizal Inoculation Enhances Nutrient Absorption and Induces Insect-Resistant Defense of Elymus nutans - Zhang, Wantong; Yu, Lu; Han, Bing; Liu, Kesi; Shao, Xinqing (Frontiers in Plant Science, 2022)
The majority of terrestrial plants can form symbiotic associations on their roots with arbuscular mycorrhizal fungi (AMF) in the soil to stimulate the growth and nutrient uptake of the host plant and to improve plant resistance to insects and disease. However, the use of AMF for insect control on gramineous forages requires further study. Here, we evaluated the effects of AMF (Funneliformis mosseae) inoculation on the defense against Locusta migratoria attack in Elymus nutans. Inoculation assays showed that mycorrhizal plants had a higher resistance than non-inoculated plants, as evidenced by plants having more plant biomass, a higher nitrogen and phosphorus content, and greater lipoxygenase (LOX) activity. The results of insect damage showed that in addition to a decrease in the enzyme phenylalanine-ammonia-lyase, the activities of other plant defense-related enzymes (including polyphenol oxidase and β-1,3-glucanase) were increased. A key enzyme, LOX, belonging to the jasmonic acid (JA) signaling pathway was notably increased in mycorrhizal treatment. Volatile organic compounds (VOCs) were identified using gas chromatography mass spectrometry and the results showed that several metabolites with insect-resistant properties, including D-Limonene, p-Xylene, 1,3-Diethylbenzene were detected in mycorrhizal plants. These findings suggest that mycorrhizal inoculation has potential applications in insect management on forage grasses and demonstrates that the JA signaling pathway is essential for insect resistance in Elymus nutans.